Devaluation of Safe Sex by Delay or Uncertainty: A Within-Subjects Study of Mechanisms Underlying Sexual Risk Behavior - Wongsomboon, Val; Robles, Elias (Archives of sexual behavior, 2017)
The value of safe sex may be discounted based on contextual factors associated with an opportunity for sex. College students in a within-subjects study selected hypothetical sexual partners from a set of pictures and classified them based on attractiveness and estimated chance of having an sexually transmitted infection (STI). In the Sexual Delay Discounting (SDD) task, participants rated their likelihood (0–100 %) of waiting for some period of time (e.g., 3 h) to have protected sex with their selected partners, when they could have immediate sex without protection. In the Sexual Probability Discounting (SPD) task, participants rated their likelihood of having protected sex if the opportunity was uncertain (e.g., 50 %), when they could have unprotected sex for sure (100 %). All participants included in the final analyses were aware of and had a positive attitude towards protection against STIs as they were likely to have immediate (or certain) protected sex. Results from 432 delay data in the SDD task and 488 probability data in the SPD task showed that participants’ preference for safe sex systematically decreased as the delay to and odds against having safe sex increased. However, this preference was altered by the participants’ perception of their partner’s attractiveness and STI risk.